Factors influencing death attitudes of medical students: a scoping review - Jingjing Tong; Qian Liu; Ying Liu; Juan Li; Qin Zhang; Huashan Shi (Frontiers Media S.A., 2024)
AimTo summarize factors influencing death attitudes of medical students, help identify intervention targets, and design precision interventions for improving death attitudes of medical students.MethodsWeb of Science, PubMed, Embase, OVID, China National Knowledge Infrastructure, and Wanfang databases were searched. Retrieval time was from January 2012 to September 2023. Studies on factors influencing death attitudes of medical students were included.ResultsThirty-five studies were included in the final review. A total of 28 factors influencing death attitudes of medical students were summarized and divided into three categories comprising personal factors, social factors, and psychological factors. More than 15 studies confirmed that gender, religion, and discussing death with families were factors that influenced medical students' death attitudes.ConclusionResults indicate that there are many types of factors that influence death attitudes of medical students. It is necessary for universities to implement death education based individual characteristics and guide medical students to cultivate generally optimistic death attitudes and appropriate life values.